The tools for improving comfort urban areas by a comprehensive indicator of environmental hazards - Гулевець, Д. В. (Problems of Environmental Biotechnology, 2013)
The article is devoted to comprehensive assessment of recreational resources on the example of Kyiv as the most populous city in Ukraine and the possibility of developing ecosystem analysis based on the latest information and GIS technologies. Considered by which to assess performance and analyzes tools that will increase the comfort of urban areas given the complex index of environmental hazards.